2001
DOI: 10.1182/blood.v97.1.169
|View full text |Cite
|
Sign up to set email alerts
|

Antigenicity of putative phospholipid membrane-binding residues in factor VIII

Abstract: Most inhibitory antibodies to human factor VIII (fVIII) bind to epitopes in the A2, ap-A3, or C2 domains. The anticoagulant action of antibodies to the C2 domain is due to inhibition of binding of fVIII to phospholipid. The x-ray structure of the human fVIII C2 domain shows a putative hydrophobic, 3-prong, phospholipid membrane-binding site consisting of Met2199/Phe2200, Val2223, and Leu2251/Leu2252. Additionally, Lys2227, near Val2223, is part of a ring of positively charged residues that may contribute to el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 31 publications
3
63
0
Order By: Relevance
“…Crystal structure analysis has demonstrated that binding of the C2 domain to phospholipid membranes involves three hydrophobic "feet" containing residues (35,36). The factor IXa-interactive site that we have identified within residues 2228 -2240 appears, therefore, to be in close proximity to, but not likely to be overlapping, the phospholipid-binding region.…”
Section: Effects Of Synthetic C2 Peptides On Rc2 and Egr-factor Ixa Imentioning
confidence: 86%
“…Crystal structure analysis has demonstrated that binding of the C2 domain to phospholipid membranes involves three hydrophobic "feet" containing residues (35,36). The factor IXa-interactive site that we have identified within residues 2228 -2240 appears, therefore, to be in close proximity to, but not likely to be overlapping, the phospholipid-binding region.…”
Section: Effects Of Synthetic C2 Peptides On Rc2 and Egr-factor Ixa Imentioning
confidence: 86%
“…This observation is consistent with the identification of a major epitope for factor VIII inhibitors in this part of factor VIII. 6,29 Based on their reactivity with factor VIII/V hybrid 8A, it is likely that residues contained within the carboxyterminus of the C2 domain also contribute to binding of DP-5-encoded scFv (Figure 3). Recently, the 3-dimensional structure of DP-5-encoded human monoclonal antibody BO2C11 in complex with the C2 domain has been determined.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the BO2C11 epitope identified here. 53 Only 2 point mutations associated with hemophilia A, A2201P and V2223M, have been identified within the antibody interface identified here. The patients carrying these mutations suffered from relatively mild bleeding disorders.…”
Section: Org Frommentioning
confidence: 99%